Argo and Zero Dark Thirty: Film, Government, and Audiences. Issue 1 (31st December 2014) - Pautz, Michelle C.
ABSTRACT: With the prevalence and accessibility of film today, we must wonder how film affects its audience. In particular, how does film influence an audience's perceptions of the government? Regardless of the content, research demonstrates that film has the power to shape perceptions of its moviegoers on a range of subjects. In this study, two recent films, Argo and Zero Dark Thirty, were chosen as case studies to explore how Hollywood portrays the intelligence community in film and shapes opinions about the government more broadly. This research found that about 25% of viewers of the two films changed their opinion about the government after watching one of the movies. Additionally, many of those changes are reflected in an improvement in the sentiments about the government and its institutions. This exploratory research provokes interesting discussions about the ability of film to influence the perceptions of an audience.